Demand for energy in Northern India - National Council of Applied Economic Research New Delhi (New Delhi, 1965)
This volume is the fourth in the series by the National Council on regional studies of demand and supply of energy in India, covering separately the four regions, the eastern, the southern, the western and the northern. The reports on the first three regions have already been published. The present study of the northern region, the last of the series, covers the States of Punjab, Rajasthan, Jammu and Kashmir and the Union Territories of Delhi and Himachal Pradesh.
Keywords: Energy